2019
DOI: 10.1002/slct.201803940
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Dentate Carbazole Based Schiff Base Dyes with Chlorovinylene Group in Spacer for Dye‐Sensitized Solar Cells: A Combined Theoretical and Experimental Study.

Abstract: Four new metal free organic Schiff bases employing N-hexyl/Nphenyl carbazole moiety as a donor, 1-chlorobuta-1,3-diene as a π-bridge and 4-amino salicylic acid as an anchor, are designed, synthesized and investigated as photosensitizers in the dye-sensitized solar cell (DSSC). We have studied the combined effect of the introduction of electronegative chlorine group with an additional double bond in π-conjugation and 4amino salicylic acid as a tridentate anchoring group, on the optoelectronic, theoretical and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…The conjugated spacers based on vinylene, ethynylene, furan, thiazole, thiophene and other fused aromatic segments (indole 87 , fluorene 88 , benzothiadiazole 89 ) showed similar peak shifts in both directions. Other groups such as diphenylquinoxaline 90 , 1-chlorobuta-1,3-diene 91 , dithienobenzotriazole 92 and dithienobenzofurazan 93 found in a limited number of cases were largely associated with red-shifted peaks. On the other hand, those containing linkers based on fused thiophene derivatives such as dithienopyrrolobenzotriazole 94 , cyclopentadithiophene 95 , thienothienopyrrole 96 , silolodithiophene 97 were blue shifted by more than 50 nm compare to the solution.…”
Section: Resultsmentioning
confidence: 97%
“…The conjugated spacers based on vinylene, ethynylene, furan, thiazole, thiophene and other fused aromatic segments (indole 87 , fluorene 88 , benzothiadiazole 89 ) showed similar peak shifts in both directions. Other groups such as diphenylquinoxaline 90 , 1-chlorobuta-1,3-diene 91 , dithienobenzotriazole 92 and dithienobenzofurazan 93 found in a limited number of cases were largely associated with red-shifted peaks. On the other hand, those containing linkers based on fused thiophene derivatives such as dithienopyrrolobenzotriazole 94 , cyclopentadithiophene 95 , thienothienopyrrole 96 , silolodithiophene 97 were blue shifted by more than 50 nm compare to the solution.…”
Section: Resultsmentioning
confidence: 97%
“…The CV was performed in an acetonitrile solution containing 0.1 N tetraethylammonium tetrafluoroborate (TEABF 4 ) at a scan rate of 20 mVs −1 . The CV results revealed that the ground state oxidation potentials ( E ox ) or highest occupied molecular orbital (HOMO) of CDIB (vs. Normal Hydrogen Electrode (NHE)) are observed at 0.827 V (Figure 2) which has significantly more positive than 0.4 V in comparison to the redox potential of the iodide/triiodide pair indicating that oxidized sensitizers can be recycled efficiently 88 . In addition, the intersection of absorption spectra was used to determine the zero‐zero excitation energy (E 0−0 ) and obtained value is 2.857 V (vs. NHE).…”
Section: Resultsmentioning
confidence: 99%
“…As a rule, the areas of electrostatic potential in terms of color increase in the order of blue > green > yellow > orange > red. [ 46–47 ] However, the areas of low potential (red color) and the areas of high potential (blue color) are characterized by abundance and dearth of electrons, respectively. From Figure 6, it is evident that the low potential was observed for all the three dyes on the electron‐accepting carboxylic acid (‐COOH) group, thus indicating the abundance of electrons in the red region of the molecule.…”
Section: Resultsmentioning
confidence: 99%